Innate Immune System Orchestrates Metabolic Homeostasis and Dysfunction in Visceral Adipose Tissue During Obesity - Zhen, Yu; Shu, Wentao; Hou, Xintong; Wang, Yinan (Frontiers in Immunology, 2021)
Arising incidence of metabolic disorders and related diseases caused by obesity is a global health concern. Elucidating the role of the immune system in this process will help to understand the related mechanisms and develop treatment strategies. Here, we have focused on innate immune cells in visceral adipose tissue (VAT) and summarized the roles of these cells in maintaining the homeostasis of VAT. Furthermore, this review reveals the importance of quantitative and functional changes of innate immune cells when the metabolic microenvironment changes due to obesity or excess lipids, and confirms that these changes eventually lead to the occurrence of chronic inflammation and metabolic diseases of VAT. Two perspectives are reviewed, which include sequential changes in various innate immune cells in the steady state of VAT and its imbalance during obesity. Cross-sectional interactions between various innate immune cells at the same time point are also reviewed. Through delineation of a comprehensive perspective of VAT homeostasis in obesity-induced chronic inflammation, and ultimately metabolic dysfunction and disease, we expect to clarify the complex interactive networks among distinct cell populations and propose that these interactions should be taken into account in the development of biotherapeutic strategies.